Application of Different Temperatures in the Incubation Process of Jurung Fish Eggs (Tor tambra) - Firdaus, Rian; Nurhatijah, Nurhatijah; Rismawati, Shela (Tomini Journal of Aquatic Science, 2021)
The habitat of the Jurung Fish (Tor tambra) is generally inflowing rivers, rocky bottom waters and relatively low water temperatures. This study aimed to determine the hatchability of the Jurung Fish (Tor tambra) eggs with different temperature treatments using a tray in the aquarium. The research method used is the laboratory experimental method and the experimental design is a non-factorial completely randomized design (CRD) consisting of 4 treatments and 4 replications: A (control), B (28°C), C (30°C) and D (32°C). The results showed that the application of different temperatures had a significant effect on the hatching of the Jurung Fish (Tor tambra) eggs. The results of Duncan's further test analysis showed that the 28°C temperature treatment was the best compared to other temperatures. This study recommends that further research is needed on larval abnormalities at different water temperatures.